The Influence of Job Characteristics and Organizational Perception Support on Employee Engagement Statistisi at the Statistics Indonesia - Purba, Rey Ronald; Hendrian, Hendrian; Rahayu, Heffi Christya (Universitas Pamulang, 2023)
This research would like to see the effect of Job Characteristics variables and perceptions of organizational support on Employee Engagement Statististis at the Statistics Indonesia. This is a quantitative research with primary data collected from a sample of 429 respondents spread throughout Indonesia (34 provinces), selected using a Systematic Random Sampling method through a survey method. The data collected were analyzed using a Likert scale of 1-5. In addition, the data were analyzed using multiple linear regression with the aid of SPSS For Windows. The variables of job characteristics and perceived organizational support have a significant effect on employee engagement statistisi at Statistics Indonesia. This study provides a new perspective on job characteristics and perceived organizational support simultaneously have a significant effect on employee engagement statistisi which has never been carried out in previous literature.